2015
DOI: 10.1128/jcm.02136-14
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Nucleic Acid Tests for Clinical Measurements of Bacteria and Viruses

Abstract: f Nucleic acid-based tests for infectious diseases currently used in the clinical laboratory and in point-of-care devices are diverse. Measurement challenges associated with standardization of quantitative viral load testing are discussed in relation to human cytomegalovirus, BK virus, and Epstein-Barr virus, while the importance of defining the performance of qualitative methods is illustrated with Mycobacterium tuberculosis and influenza virus. The development of certified reference materials whose values ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Interlaboratory comparisons are needed to determine the repeatability and reproducibility of analytical methods to be standardised . In our reference laboratory, we obtained 72.1% of total matches when analysing purified DNA by LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Interlaboratory comparisons are needed to determine the repeatability and reproducibility of analytical methods to be standardised . In our reference laboratory, we obtained 72.1% of total matches when analysing purified DNA by LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using dPCR, Hayden et al [7] showed that commonly used standard curves for CMV quantification by qPCR produce variable results. Nowadays, dPCR has been suggested as a reference measurement procedure to certify new standards [51]. In addition, dPCR can be used as a reference method to assess the commutability of reference standards for qPCR, i.e.…”
Section: Quantitative Accuracymentioning
confidence: 99%
“…A wide range of methodologies to quantify EDLs are used in laboratories. Given this heterogeneity, comparison of EDL results between different laboratories is difficult (11)(12)(13)(14). Interlaboratory variability in EDL testing should be reduced to establish consensus therapeutic or interventional thresholds between different medical centers for the management of PTLDs.…”
mentioning
confidence: 99%